2023
DOI: 10.3390/ijms24044011
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Organization of the B10v3 Cucumber Genome by Integration of Biological and Bioinformatic Data

Abstract: The availability of a well-organized and annotated reference genome is essential for genome research and the analysis of re-sequencing approaches. The B10v3 cucumber (Cucumis sativus L.) reference genome has been sequenced and assembled into 8035 contigs, a small fraction of which have been mapped to individual chromosomes. Currently, bioinformatics methods based on comparative homology have made it possible to re-order the sequenced contigs by mapping them to the reference genomes. The B10v3 genome (North-Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Cucumis sativus, commonly known as cucumber, is characterised by well-established reference lines, such as 9930 (a Chinese line) and Gy14 (a North American line) and the longest B10v3 (North European) [49][50][51]. Recently, a system for integrating experimental data with high-throughput genomic data was used by Turek et al [52], where a model of genome comparison and a merging of experimental data were proposed [52]. As more and more genomes are sequenced and assembled, comparative genomics methods and adaptive genome drafts are increasingly needed to standardise gene location and annotation information.…”
Section: Cucurbits Genomes Complexity and Characterisationmentioning
confidence: 99%
“…Cucumis sativus, commonly known as cucumber, is characterised by well-established reference lines, such as 9930 (a Chinese line) and Gy14 (a North American line) and the longest B10v3 (North European) [49][50][51]. Recently, a system for integrating experimental data with high-throughput genomic data was used by Turek et al [52], where a model of genome comparison and a merging of experimental data were proposed [52]. As more and more genomes are sequenced and assembled, comparative genomics methods and adaptive genome drafts are increasingly needed to standardise gene location and annotation information.…”
Section: Cucurbits Genomes Complexity and Characterisationmentioning
confidence: 99%
“…Recently, genomes were compared using structural data presented in databases as well as previously reported experimental data. It was shown that the B10v3 genome was the longest due to its 342.5 Mbp assembled length [ 4 ]. Among others, in order to obtain the most complete picture of the relevant elements, in this study, we focused on this version of the genome for further analyses.…”
Section: Introductionmentioning
confidence: 99%
“…About 94% of the cucumber genome is covered by B10 and is considered the most comprehensive draft version to date ( Osipowski et al, 2020 ). Recently, Turek et al (2023) gave more insight into the genome of B10v3 accession by comparing it with the genome of cucumber lines Gy-14 and 9930. Recent advances in genome sequencing have provided stimulating opportunities to accelerate research in cucumber breeding.…”
Section: Introductionmentioning
confidence: 99%